Synergism of virgin coconut oil and mulberry leaves extract as agent in free alcohol hand sanitizer / Norhazlin Jusoh ...[et al.] - Jusoh, Norhazlin; Mohamad Mahbob, Emi Norzehan; Ahmad Zulkifli, Farah Zayanah; Rosman, Putri Shareen; Zulkipli, Husna (Universiti Teknologi MARA Cawangan Kelantan, 2019)
Hand hygiene is foremost techniques in preventing the spread of any health care-associated infections and keeping the health cost under control. Hand sanitizer is the key for hand hygiene when limited resources and water access. The problem is alcohol-based hand sanitizer can cause health issues such as drying skin and alcoholic poisoning. Therefore, alcohol-free hand sanitizer becomes the next approach. Investigations on hand sanitizer without alcohol for their effectiveness on microorganism‟s infection are still scarce. Hence, the main objective of this study is to investigate the effectiveness of alcohol-free hand sanitizer on microbial hands carriage. The main focus is on inhibiting the growth of pure cultured bacteria from hands which were Streptococcus sp. and Staphylococcus sp. Production of alcohol-free hand sanitizer using natural products (virgin coconut oil and mulberry leaves extract) as antibacterial agents as an alternative to the current hand sanitizers in market. In the study, the antibacterial activity of alcohol-free hand sanitizer was compared with clinical hand sanitizer, commercial hand sanitizer and sterile water using disc diffusion method. Undoubtedly, clinical hand sanitizer showed the highest inhibition zone with 21 mm for both types of bacteria. On the other hand, alcohol-free hand sanitizer and commercial hand sanitizer surprisingly obtained almost similar size of inhibition zone with 14-14.5 mm. As conclusion, the alcohol-free hand sanitizer was effective in resisting the bacterial growth on hands and as promising option particularly in health impacts after use. The tested product can be introduced to selected market segments for example local pharmacies, clinics and hospitals